TEUNGKU CHIEK DIRUNDENG: SEJARAH DAN PERAN TERHADAP PENDIDIKAN - Syamsuar Syamsuar (Universitas Islam Negeri Ar-Raniry, 2019)
This research is talking about the study of Teungku Chiek Dirundeng which discussed about his life history and his influence in the education world. Teungku Chiek Dirundeng is one of the theologians or ulama who has been developed human civilization and human education by using dayah. This study used qualitative methods This research used qualitative method, it told about his history, his birth and his influence toward educaton. The data collected through interviews, observation and Focus Group Discussion (FGD). The findings of this study were Teungku Chiek Dirundeng was a theologian who had appellation name “Teungku” and he was an aristocrat who had appellation name “Teuku”. On the other hand, Teungku Chiek Dirundeng was also known he was very generous figure. The generosity meant that he had donated and granted his treasures for communities or umat needs. Furthermore, his influence in education world, he had built many boarding schools or dayah in Aceh. Particularly in Meukek, Labuhan Haji and Rundeng.